Healthcare Utilization, Costs of Care, and Mortality Among Patients With Spinal Muscular Atrophy - Hiangkiat Tan; Tao Gu; Er Chen; Rajeshwari Punekar; Perry B. Shieh (Journal of Health Economics and Outcomes Research)
# Objectives To understand treatment patterns, healthcare resource utilization, and costs of care among patients with spinal muscular atrophy (SMA).